Application of Arsenic Trioxide-Based Combined Sequential Chemotherapy in Recurrent Resistant and Refractory Ovarian Cancers: A Single-Center, Open Phase II Clinical Study. (31st August 2022) - Yang, Yingchao; Li, Xiaoping; Wang, Yue; Shen, Xiaoyan; Zhao, Lijun; Wu, Yan; Li, Yi; Wang, Jianliu; Wei, Lihui
Abstract : Objective . Arsenic trioxide (ATO) has been effectively used for the treatment of hematological malignancies and some solid tumors, while ATO effects were not tested clinically in epithelial ovarian cancer (EOC). Methods . Patients with primary or secondary platinum-resistant EOC were enrolled from October 2015 to December 2019. Patients were mainly treated with ATO-based combined sequential chemotherapy as follows: Regimen 1 (ATO combined taxanes weekly therapy); Regimen 2 (ATO + taxanes + 5-fluorouracil + adriamycin ± bevacizumab sequential chemotherapy), for 5 patients platinum-free interval >12 months, added oxaliplatin). Prespecified end points in this cohort included confirmed best overall response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and safety. Results . A total of 33 patients were enrolled in this study. After a median follow-up time of 22.1 months (range 5.5–42.9 months), ORR was 42% and DCR was 85%. The overall PFS was 9.5 months (range 1–38.4 months). The main side effect was myelosuppression. Conclusions . ATO-based sequential combined chemotherapy is effective for primary and recurrent drug-resistant EOC patients in clinical phase II trials. The associated side effects could be controlled, while further study is needed.